Ditinggalkan tapi Tidak Sendirian: Mazmur 27:10 dan Gambaran Kehilangan Orang Tua - Suryawinata, Samuel (STT Reformed Injili Internasional, 2025)
Losing a parent is one of the most painful experiences in a person's life. Its impact can raise a profound existential question: